A Case Demonstrating the Pathological Relationship between Granulomatous Vasculitis and Glomerular Lesion in Renal Sarcoidosis - Yoshinori Kamata; Hiroshi Sato; Akira Sugiura; Masahiro Miyata; Kiyomi Kisu; Arata Azuma (Case Reports in Nephrology and Dialysis, 2020)
We experienced a rare case of tubulointerstitial angiocentric granulomatous vasculitis with focal segmental glomerulosclerosis (FSGS) and associated sarcoidosis. Our patient was an 18-year-old man who presented with exertional cough and dyspnea. He also had overt proteinuria (3.0 g/24 h), normal renal function (eGFR 95 mL/min/1.73 m2), heart failure, and hypertension. He had no previous episode of hypertension. These manifestations immediately improved after the administration of antihypertensive therapy that contained an angiotensin-converting enzyme inhibitor, calcium antagonists, beta antagonists, and diuretics. However, he, later on, developed renal dysfunction, with worsening of both proteinuria and hypertension. Renal biopsy was performed and showed epithelioid cells that were arranged concentrically around small blood vessels in tubulointerstitial granulomas. In the glomeruli, the segmental sclerotic lesions were classified as a perihilar variant of FSGS. There were no inflammatory changes, such as a mesangial lesion, inflammatory cell infiltration, fibrinoid necrosis, or crescent formation, and no glomerular granuloma. In the tubulointerstitial granulomas, the intimal elastic lamina of the interlobular arteries was reduplicated, and the intimal wall thickness of renal arterioles was remarkable. After receiving oral prednisolone therapy, the overt proteinuria resolved, the eGFR recovered from 39.4 to 60.6 mL/min/1.73 m2, and hypertension was managed more easily. Thereafter, he did not experience any recurrence. The concurrent improvement of renal function and proteinuria by steroid treatment suggested a relationship between the glomerular lesions and the tubulointerstitial granulomatous vasculitis with associated sarcoidosis.